Is vertical jump height an indicator of athletes' power output in different sports modalities? - Kons, R. L.; Ache-Dias, J.; Detanico, D.; Barth, J.; Dal Pupo, J. (The Journal of Strength and Conditioning Research, 2018)
This study aimed to identify whether the ratio standard is adequate for the scaling of peak power output (PPO) for body mass (BM) in athletes of different sports and to verify classification agreement for athletes involved in different sports using PPO scaled for BM and jump height (JH). One hundred and twenty-four male athletes divided into 3 different groups—combat sports, team sports, and runners—participated in this study. Participants performed the countermovement jump on a force plate. Peak power output and JH were calculated from the vertical ground reaction force. We found different allometric exponents for each modality, allowing the use of the ratio standard for team sports. For combat sports and runners, the ratio standard was not considered adequate, and therefore, a specific allometric exponent for these 2 groups was found. Significant correlations between adjusted PPO for BM (PPOADJ) and JH were found for all modalities, but it was higher for runners (r = 0.81) than team and combat sports (r = 0.63 and 0.65, respectively). Moderate agreement generated by the PPOADJ and JH was verified in team sports (k = 0.47) and running (k = 0.55) and fair agreement in combat sports (k = 0.29). We conclude that the ratio standard seems to be suitable only for team sports; for runners and combat sports, an allometric model seems adequate. The use of JH as an indicator of power output may be considered reasonable only for runners.